2017
DOI: 10.21273/horttech03809-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colored Shadecloth on the Quality and Yield of Lettuce and Snapdragon

Abstract: Colored shadecloths are used in the production of vegetable, fruit, and ornamental crops to manipulate the light spectrum and to induce specific plant physiological responses. The influence of three colored shadecloths (red, blue, and black) with 50% shade and a no-shade control on the production of two lettuce (Lactuca sativa) cultivars [Two Star (green-leaf) and New Red Fire (red-leaf)] and snapdragon (Antirrhinum majus) was investigated. Use of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
3
11
4
1
Order By: Relevance
“…CHS is the first step in the flavonoid biosynthesis pathway [31] and previous studies have found that both blue light and UV-A light enhance the response of CHS to UV-B synergistically [28,32]. It has been shown that full-spectrum, solar radiation can increase the amounts of certain phenolic compounds, such as flavonoids and phenolic acids due to photo-oxidative stress [30,[33][34][35][36]. However, responses are crop and species specific, and it has been suggested that solar UV-B may be insufficient to promote flavonoid production [37], therefore, supplemental radiation may be needed for increased accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…CHS is the first step in the flavonoid biosynthesis pathway [31] and previous studies have found that both blue light and UV-A light enhance the response of CHS to UV-B synergistically [28,32]. It has been shown that full-spectrum, solar radiation can increase the amounts of certain phenolic compounds, such as flavonoids and phenolic acids due to photo-oxidative stress [30,[33][34][35][36]. However, responses are crop and species specific, and it has been suggested that solar UV-B may be insufficient to promote flavonoid production [37], therefore, supplemental radiation may be needed for increased accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Photo-selective, coloured, shade nets provide diverse mixtures of natural, unmodified light and scattered, spectrally modified light (Ilić and Fallik, 2017). Spectral modification promotes physiological responses which affects productivity and quality (Li et al, 2017). Accumulation of phytochemicals depends on many factors, such as light quality and quantity, type of varieties or cultivars, growing season and metabolic factors (Simakumar and Jifon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Inicialmente, as redes fotosseletivas eram brancas, pretas ou do tipo Aluminet ® (Ganelevin, 2006;Li et al, 2017). No ano de 1996, redes coloridas como vermelha, amarela, azul e pérola (ChromatiNet ® ) foram introduzidas para absorver e alterar, o espectro e a Research, Society and Development, v. 9, n. 8, e590985921, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5921 radiação que atinge às plantas, devido a uma parceria entre pesquisadores e a indústria (Ganelevin, 2006;Manja & Aoun, 2019).…”
Section: Introductionunclassified